Computed tomography reconstruction and morphometric analysis of the humerus and femur in new zealand rabbits - Muhammet Lutfi Selcuk (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to create three-dimensional (3D) models of the humerus and femur using computed tomography (CT) images of the New Zealand rabbit and to reveal whether there are differences between sexes and the right and left sides. Materials and Methods: The study was applied on 14 month old (10 male and 10 female) New Zealand rabbits. First, 0.5 mm thick images of the animals were taken by computed tomography (CT) and saved in DICOM format. Then, 3D models of the humerus and femur were obtained by reconstructing the images with the MIMICS 20.1 program. Morphometric data were obtained from the obtained 3D model. After this procedure, the rabbits were dissected and the weights of the humerus and femur were measured. Results: It was determined that the right humerus and femur volume and surface area in male rabbits were larger from the left side (p<0.05). There was no difference between the other morphometric values examined and rabbit bones did not show homotypic variation. In addition, it was thought that the humerus and femur bones could not be used to determine gender because the differences between the sexes were insignificant. Conclusion: It was thought that this study would provide the basis for studies and experimental models on rabbits by revealing the morphological features of the humerus and femur and would help the physician in the diagnosis of diseases by forming the basis of the data obtained with the imaging systems used in the clinical field.